JIGSAW AND TGT METHOD IN WRITING DESCRIPTIVE ABILITY OF HIGH SCHOOL STUDENTS - Yunita Sari; Arif Fatoni (SIGEH ELT : Journal of Literature and Linguistics, 2022)
The researchers assume that ability of writing should be developed in a good plan and through practices. The most important duty for his effort to minimize students’ difficult in writing. It was got indication that learning form was done still traditional. The using of learning strategy gives possibility to students’ to relate and apply their knowledge and skill that they got at the class with real life that are in their environment. Teacher’s duty is a facilitator that gives direction and graduate to the students’, so the English learning contextually can be applied correctly to become more effective. It is expected the implementation of this research is through contextual teaching and learning approach can increase students’ ability in writing descriptive.